Plans for country homes in the semi-arid region - Gammon, Erma (My University, 1908)
Introduction: The impression made upon the stranger’s mind as he travels though the semi-arid region is one of loneliness and isolation. Few, mean low and scrubby treed are scattered along the scanty streams, often only one tree being seen and these in thin patches far apart.
Citation: Gammon, Erma. Plans for country homes in the semi-arid region. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Construction; Blueprints; Buildings; Handwritten; Graduating theses; Senior theses; Theses